Implications of entropy generation in bioconvective flow on Maxwell nanofluid past a Riga plate with Cattaneo--Christov model - K. Loganathan; Prasun Choudhary; S. Eswaramoorthi; K. Senthilvadivu; N. Thamaraikannan; Reema Jain (Partial Differential Equations in Applied Mathematics)
This study explores the effects of heat and mass transfer in the flow of Maxwell nanofluid over a heated Riga plate. The fluid contains nanoparticles and gyrostatic microorganisms. It examines how these components influence the flow's thermal and mass transfer properties. The heat and mass fluxes are regarded as a non-Fourier model. Governing model is formulated as a system of partial differential equations. By employing suitable transformations, these partial differential equations are transformed into a set of standard ordinary differential equations. The derived system of ordinary differential equations is resolved utilizing convergent series solution via an analytical method known as the homotopy analysis method (HAM). The graphs illustrate the impact of several physical parameters on flow profiles, emphasizing their unique properties. This article offers several significant conclusions as the mixed convection parameter λ increases, flow velocity rises. Conversely, higher inputs of the thermal relaxation parameter Γ1 take towards to a reduction into temperature profile. An increment in the data of bioconvection Lewis number Lb results in a decrease in microorganism concentration, while the thermophoresis parameter Nt has the opposite effect, increasing the microorganism profile. Further, it is examined that in the presence of Hartmann number, velocity profile dominate those observed in its absence, whereas temperature profiles exhibit a reverse scenario.